School homework: the reflection of an educational system - Polo Martínez, Ignacio; Bailén, Eva (Avances en Supervisión Educativa, 2016)
The Spanish education system has become one of the worst, as evaluated by the PISA-OCDE assessments. The tip of the iceberg of this education systemwhich constantly proves to have truly poor results- is showing itself in the children’s homes, by the assignment of homework. Despite the fact that an increasing number of studies show evidence that assigning homework to primary school children (especially the youngest ones) is useless, Spanish primary school students are overwhelmed with their school duties. Likewise, the World Health Organisation has reported that secondary school students feel they are living under high pressure due to their school responsibilities. It is imperative to enforce a change in the Spanish education system, with a clear aim of reducing homework load and students’ stress levels. Promoting the right change will provide the Spanish education system with better results and achieve students’ proper wellbeing.